Positive electrode active material for non-aqueous electrolyte secondary battery, and non-aqueous electrolyte secondary battery

By adding Ca and Sr to the lithium transition metal composite oxide and adjusting its distribution characteristics, the problem of side reaction of lithium transition metal composite oxide with high Ni content in the non-aqueous electrolyte is solved, and the charge and discharge cycle characteristics are realized. Improved power characteristics.

CN119404338APending Publication Date: 2025-02-07PANASONIC INTELLECTUAL PROPERTY MANAGEMENT CO LTD
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202380047660.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2022-06-29
Filing Date
2023-06-16
Publication Date
2025-02-07

AI Technical Summary

Technical Problem

Lithium transition metal composite oxides with Ni content of more than 80% are prone to side reactions in the non-aqueous electrolyte, resulting in a decrease in charge and discharge cycle characteristics and an increase in resistance.

Method used

The positive electrode active substance containing Ni, Ca and Sr in the lithium transition metal composite oxide was used, and the distribution of Ca and Sr was adjusted by time-of-flight secondary ion mass spectrometry to make the Gini coefficient on the surface of the secondary particles less than 0.7. The internal Gini coefficient is less than 0.6.

Benefits of technology

The charge and discharge cycle characteristics and power characteristics of the nonaqueous electrolyte secondary battery are improved, and the rise of resistance is suppressed.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119404338A_ABST
    Figure CN119404338A_ABST
Patent Text Reader

Abstract

Provided is a positive electrode active material that improves charge / discharge cycle characteristics of a non-aqueous electrolyte secondary battery and suppresses an increase in resistance. The positive electrode active material contained in the nonaqueous electrolyte secondary battery contains a lithium transition metal composite oxide, the lithium transition metal composite oxide contains Ni, Ca, and Sr, and contains secondary particles formed by aggregating primary particles, and in the element concentration distribution in the cross section of the lithium transition metal composite oxide using time-of-flight secondary ion mass spectrometry, the element concentration distribution in the cross section of the lithium transition metal composite oxide is less than the element concentration distribution in the cross section of the lithium transition metal composite oxide, and the element concentration distribution is less than the element concentration distribution in the cross section of the lithium transition metal composite oxide. The Gini coefficient of the surface of the secondary particles of Ca and Sr is 0.7 or less, and the Gini coefficient of the interior of the secondary particles of Ca and Sr is 0.6 or less.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present disclosure relates to a positive electrode active material for a nonaqueous electrolyte secondary battery and a nonaqueous electrolyte secondary battery. Background Art

[0002] It has long been known that lithium nickel oxide (LiNiO2) has a high energy density, and battery characteristics such as reliability can be improved by replacing part of Ni with Co, Al, Mn, etc.

[0003] Patent Document 1 discloses a technique for improving the charge-discharge cycle characteristics and safety of a secondary battery by using a positive electrode active material in which Sr is solid-dissolved at a predetermined ratio in an NCM-based lithium transition metal composite oxide containing Ni, Co, and Mn.

[0004] Prior art literature

[0005] Patent Literature

[0006] Patent Document 1: Japanese Patent No. 6226430 Summary of the invention

[0007] However, lithium transition metal composite oxides with a Ni content of more than 80% are prone to side reactions with non-aqueous electrolytes, so that charge-discharge cycle characteristics are reduced and resistance increases are sometimes a problem. The technology described in Patent Document 1 does not study the improvement of battery characteristics using lithium transition metal composite oxides with a high Ni content, and there is still room for improvement.

[0008] An object of the present disclosure is to provide a positive electrode active material that improves the charge-discharge cycle characteristics of a nonaqueous electrolyte secondary battery and suppresses an increase in resistance.

[0009] A positive electrode active material for a non-aqueous electrolyte secondary battery as one embodiment of the present invention is characterized in that it comprises a lithium transition metal composite oxide, the lithium transition metal composite oxide contains Ni, Ca and Sr, and comprises secondary particles formed by aggregation of primary particles, and in the element concentration distribution of the cross section of the lithium transition metal composite oxide using time-of-flight secondary ion mass spectrometry, the Gini coefficient of the secondary particle surface of Ca and Sr is less than 0.7, and the Gini coefficient of the secondary particles inside Ca and Sr is less than 0.6.

[0010] A nonaqueous electrolyte secondary battery as one embodiment of the present disclosure is characterized by comprising a positive electrode including the positive electrode active material for a nonaqueous electrolyte secondary battery, a negative electrode, and a nonaqueous electrolyte.

[0011] According to the positive electrode active material for a nonaqueous electrolyte secondary battery as one embodiment of the present disclosure, the charge and discharge cycle characteristics and power characteristics of the nonaqueous electrolyte secondary battery can be improved. BRIEF DESCRIPTION OF THE DRAWINGS

[0012] Figure 1 It is a longitudinal cross-sectional view of a nonaqueous electrolyte secondary battery as an example of an embodiment. DETAILED DESCRIPTION

[0013] In the layered structure of the lithium transition metal composite oxide, there are a transition metal layer, a Li layer, and an oxygen layer. The Li ions present in the Li layer reversibly enter and exit, so that the charge and discharge reaction of the battery is carried out. Generally, lithium transition metal composite oxides with Ni as the main component are known as high-capacity positive electrode active materials. However, lithium transition metal composite oxides with a Ni content of more than 80% are prone to side reactions with non-aqueous electrolytes. Therefore, the products produced by the side reactions adhere to the surface of the lithium transition metal composite oxide, sometimes resulting in a decrease in charge and discharge cycle characteristics and an increase in resistance.

[0014] Patent Document 1 discloses a technique for improving the charge-discharge cycle characteristics and safety of a secondary battery by using a positive electrode active material in which Sr is solid-dissolved at a predetermined ratio in a NCM-based lithium transition metal composite oxide containing Ni, Co, and Mn. However, Patent Document 1 does not study the improvement of battery characteristics using a lithium transition metal composite oxide with a high Ni content, and there is still room for improvement.

[0015] The inventors of the present invention have conducted in-depth research to solve the above problems and found that by using a lithium transition metal composite oxide in which Ca and Sr are present at a predetermined ratio on the surface and inside of secondary particles, the charge-discharge cycle characteristics are improved and the increase in resistance is suppressed. It is presumed that the side reaction with the non-aqueous electrolyte during charge and discharge is suppressed by the synergistic effect of Ca and Sr.

[0016] Hereinafter, an example of an embodiment of the non-aqueous electrolyte secondary battery disclosed in the present invention is described in detail. Hereinafter, a cylindrical battery in which a wound electrode body is accommodated in a cylindrical outer shell is exemplified, but the electrode body is not limited to the wound type, and may also be a stacked type in which a plurality of positive electrodes and a plurality of negative electrodes are alternately stacked one by one through a separator. In addition, the outer shell is not limited to a cylindrical shape, and may be, for example, a square shape, a coin shape, etc., or may be a battery shell composed of a laminate sheet including a metal layer and a resin layer.

[0017] Figure 1 FIG. 1 is an axial cross-sectional view of a cylindrical secondary battery 10 as an example of an embodiment. Figure 1As shown, the secondary battery 10 comprises: a wound electrode body 14, an electrolyte, and an outer case 16 for accommodating the electrode body 14 and the electrolyte. The electrode body 14 includes a positive electrode 11, a negative electrode 12, and a separator 13, and has a wound structure in which the positive electrode 11 and the negative electrode 12 are spirally wound with the separator 13 interposed therebetween. The outer case 16 is a metal container in a bottomed cylindrical shape with one side open in the axial direction, and the opening of the outer case 16 is blocked by a sealing body 17. In the following, for the sake of convenience of description, the sealing body 17 side of the battery is regarded as the upper side, and the bottom side of the outer case 16 is regarded as the lower side.

[0018] The positive electrode 11, the negative electrode 12 and the separator 13 constituting the electrode body 14 are all rectangular strips, and are alternately stacked along the radial direction of the electrode body 14 by spirally winding along the length direction. The separator 13 separates the positive electrode 11 and the negative electrode 12 from each other. The negative electrode 12 is formed to be one size larger than the positive electrode 11 to prevent lithium precipitation. That is, the negative electrode 12 is formed to be longer than the positive electrode 11 in the length direction and the width direction. Two separators 13 are formed to be at least one size larger than the positive electrode 11, for example, arranged in a manner of sandwiching the positive electrode 11. The electrode body 14 includes a positive electrode lead 20 connected to the positive electrode 11 by welding or the like, and a negative electrode lead 21 connected to the negative electrode 12 by welding or the like. In the electrode body 14, the length direction of the positive electrode 11 and the negative electrode 12 is the winding direction, and the width direction of the positive electrode 11 and the negative electrode 12 is the axial direction. That is, the end faces of the positive electrode 11 and the negative electrode 12 in the width direction form the end faces of the electrode body 14 in the axial direction.

[0019] Insulating plates 18 and 19 are disposed above and below the electrode body 14 , respectively. Figure 1 In the example shown, the positive electrode lead 20 extends to the sealing body 17 side through the through hole of the insulating plate 18, and the negative electrode lead 21 extends to the bottom side of the outer shell 16 through the outer side of the insulating plate 19. The positive electrode lead 20 is connected to the lower surface of the internal terminal plate 23 of the sealing body 17 by welding or the like, and the top plate of the sealing body 17, that is, the cover 27 electrically connected to the internal terminal plate 23 serves as the positive terminal. The negative electrode lead 21 is connected to the bottom inner surface of the outer shell 16 by welding or the like, and the outer shell 16 serves as the negative terminal.

[0020] A gasket 28 is provided between the outer shell 16 and the sealing body 17 to ensure the airtightness inside the battery. A groove portion 22 is formed on the outer shell 16, with a portion of the side portion bulging inwardly for supporting the sealing body 17. The groove portion 22 is preferably formed in a ring shape along the circumferential direction of the outer shell 16, and the sealing body 17 is supported by its upper surface. The sealing body 17 is fixed to the upper part of the outer shell 16 by the groove portion 22 and the open end of the outer shell 16 that is tightly fitted to the sealing body 17.

[0021] The sealing body 17 has a structure in which an internal terminal plate 23, a lower valve body 24, an insulating member 25, an upper valve body 26 and a cover 27 are stacked in order from the electrode body 14 side. The components constituting the sealing body 17 have, for example, a disc shape or a ring shape, and the components except the insulating member 25 are electrically connected to each other. The lower valve body 24 and the upper valve body 26 are connected at their respective central portions, and an insulating member 25 is sandwiched between their respective peripheral portions. When the internal pressure of the battery rises due to abnormal heat release, the lower valve body 24 is deformed and broken in a manner that pushes the upper valve body 26 toward the cover 27 side, thereby blocking the current path between the lower valve body 24 and the upper valve body 26. When the internal pressure rises further, the upper valve body 26 breaks, and the gas is discharged from the opening of the cover 27.

[0022] Hereinafter, the positive electrode 11 , the negative electrode 12 , the separator 13 , and the nonaqueous electrolyte constituting the secondary battery 10 , particularly the positive electrode 11 , will be described in detail.

[0023] [positive electrode]

[0024] The positive electrode 11 includes, for example, a positive electrode current collector and a positive electrode mixture layer formed on the surface of the positive electrode current collector. The positive electrode mixture layer is preferably formed on both sides of the positive electrode current collector. The positive electrode current collector may be a foil of a metal such as aluminum or an aluminum alloy that is stable within the potential range of the positive electrode 11, or a thin film having the metal disposed on the surface. The thickness of the positive electrode current collector is, for example, 10 μm to 30 μm.

[0025] The positive electrode mixture layer includes, for example, a positive electrode active material, a conductive agent, and a binder. The thickness of the positive electrode mixture layer is, for example, 10 μm to 150 μm on one side of the positive electrode collector. The positive electrode 11 can be manufactured, for example, as follows: a positive electrode mixture slurry including a positive electrode active material, a conductive agent, etc. is applied to the surface of the positive electrode collector, and after the coating is dried, it is rolled to form a positive electrode mixture layer on both sides of the positive electrode collector, thereby being manufactured.

[0026] Examples of the conductive agent contained in the positive electrode mixture layer include carbon black (CB), acetylene black (AB), Ketjen black, carbon nanotubes (CNT), graphene, graphite and other carbonaceous particles, etc. These may be used alone or in combination of two or more.

[0027] As the binder contained in the positive electrode mixture layer, for example, fluorine resins such as polytetrafluoroethylene (PTFE) and polyvinylidene fluoride (PVDF), polyimide resins, acrylic resins, polyolefin resins, polyacrylonitrile (PAN), etc. can be cited. These can be used alone or in combination of two or more.

[0028] The positive electrode active material contained in the positive electrode mixture layer includes a lithium transition metal composite oxide. The lithium transition metal composite oxide contains Ni, Ca, and Sr.

[0029] The content of Ni in the lithium transition metal composite oxide is 80 mol% or more relative to the total molar number of metal elements other than Li. Thus, the battery capacity can be improved. The content of Ni is preferably 85 mol% or more, more preferably 90 mol% or more. In addition, from the viewpoint of structural stabilization, the content of Ni is preferably 95 mol% or less.

[0030] The content of Ca in the lithium transition metal composite oxide is preferably 0.01 mol% to 1 mol%, more preferably 0.1 mol% to 0.5 mol%, and further preferably 0.2 mol% to 0.4 mol%, based on the total molar number of metal elements excluding Li.

[0031] The content of Sr in the lithium transition metal composite oxide is preferably 0.01 mol% to 1 mol%, more preferably 0.02 mol% to 0.5 mol%, and further preferably 0.05 mol% to 0.2 mol%, based on the total molar number of metal elements excluding Li.

[0032] The lithium transition metal composite oxide may further include one or more elements selected from the group consisting of Co, Al and Mn. The contents of Co, Al and Mn in the lithium transition metal composite oxide are, for example, 0 mol% to 10 mol% relative to the total molar number of metal elements other than Li. In addition, the total contents of Co, Al and Mn are, for example, 0 mol% to 18 mol%.

[0033] The lithium transition metal composite oxide may further include one or more elements selected from the group consisting of Nb, Ti, Zr, W and Si. The contents of Nb, Ti, Zr, W and Si in the lithium transition metal composite oxide are, for example, 0 mol% to 1 mol% relative to the total molar number of metal elements other than Li. In addition, the total contents of Nb, Ti, Zr, W and Si are, for example, 0 mol% to 2 mol%.

[0034] Lithium transition metal composite oxides are, for example, of the general formula Li a Ni x M1 y M2 z Ca s Sr t O 2-b(wherein, 0.8≤a≤1.2, 0.80≤x≤0.95, 0≤y≤0.18, 0≤z≤0.02, 0.0001≤s≤0.01, 0.0001≤t≤0.01, 0≤b≤0.05, x+y+z+s+t=1, M1 is one or more elements selected from the group consisting of Co, Al and Mn, and M2 is one or more elements selected from the group consisting of Nb, Ti, Zr, W and Si). The ratio of the metal elements contained in the lithium transition metal composite oxide can be measured, for example, using an inductively coupled plasma emission spectrophotometer (ICP-AES).

[0035] The lithium transition metal composite oxide contains secondary particles formed by the aggregation of primary particles. The particle size of the primary particles is, for example, 0.02 μm to 2 μm. The particle size of the primary particles is measured as the diameter of the circumscribed circle in the particle image observed by a scanning electron microscope (SEM). The average particle size of the secondary particles is, for example, 2 μm to 30 μm. Here, the average particle size refers to the volume-based median particle size (D50). D50 refers to the particle size at which the accumulation of frequencies in the volume-based particle size distribution becomes 50% from the smaller particle size, and is also called the median diameter. The particle size distribution of the secondary particles can be measured using a laser diffraction particle size distribution measuring device (e.g., MT3000II manufactured by MicrotracBEL Corp.) using water as the dispersion medium.

[0036] Ca and Sr exist on the surface and inside the secondary particles. Ca and Sr exist inside the secondary particles, for example, on the surface of the primary particles and are not dissolved in the primary particles. As a result, the effect of suppressing the side reaction of the non-aqueous electrolyte and the lithium transition metal composite oxide becomes obvious. Ca can exist on the surface and inside the secondary particles as a compound containing Ca. Examples of compounds containing Ca include CaO, CaCO3, etc. Sr can exist on the surface and inside the secondary particles as a compound containing Sr. Examples of compounds containing Sr include SrO, SrCO3, etc. The presence of Ca and Sr on the surface and inside the secondary particles can be confirmed by, for example, energy dispersive X-ray spectroscopy (TEM-EDX) in addition to the time-of-flight secondary ion mass spectrometry described later.

[0037] In the element concentration distribution of the cross section of the lithium transition metal composite oxide using time-of-flight secondary ion mass spectrometry (TOF-SIMS), the Gini coefficient of the secondary particle surface of Ca and Sr is less than 0.7, and the Gini coefficient of the secondary particle inside of Ca and Sr is less than 0.6. As a result, the charge and discharge cycle characteristics are improved and the increase in resistance is suppressed. The power characteristics are improved due to the suppression of the increase in resistance. Inference: On the surface of the secondary particles and inside the secondary particles, the primary particle surface including the secondary particle surface is properly protected.

[0038] The Gini coefficient of the secondary particle surface of Ca is a value obtained as follows: the normalized intensity I of Ca on the secondary particle surface Ca_OUT , when the cumulative rate is expressed in sequence according to the intensity, the value obtained by doubling the area enclosed by the diagonal line and the Lorentz curve. The Gini coefficient of the secondary particle surface of Sr can be calculated in the same way as the Gini coefficient of the secondary particle surface of Ca mentioned above. The Gini coefficient inside the secondary particle of Ca is the value obtained as follows: for the normalized intensity of Ca inside the secondary particle, when the cumulative rate is expressed in sequence according to the intensity, the value obtained by doubling the area enclosed by the diagonal line and the Lorentz curve. The Gini coefficient inside the secondary particle of Sr can be calculated in the same way as the Gini coefficient inside the secondary particle of Ca mentioned above. The Gini coefficient becomes 0 in the case of complete uniformity, and the value increases as the uniformity decreases. The Gini coefficient inside the secondary particle of Ca can also be smaller than the Gini coefficient inside the secondary particle of Sr. That is, Ca can be more evenly dispersed inside the secondary particle than Sr. In addition, the Gini coefficient inside the secondary particle of Ca can also be smaller than the Gini coefficient on the surface of the secondary particle of Ca. That is, Ca can be more evenly dispersed inside the secondary particle than on the surface of the secondary particle.

[0039] The normalized intensity ratio of Ca and Sr was obtained by measurement under the following conditions using a time-of-flight secondary ion mass spectrometer (TOF-SIMS5 manufactured by IONTOF Corporation).

[0040] Primary ion: Bi3 +

[0041] Ion voltage: 30kV

[0042] Ion current: 0.03pA @ 100us

[0043] Observation range: 50μm×50μm

[0044] Mass range: 60us (~310amu)

[0045] Detection: 4frame / scan, 150scan

[0046] The image showing the concentration distribution of Ni, Ca and Sr obtained in the above measurement was divided into 256×256 pixels, and the detection intensity of Ni, Ca and Sr was calculated for each pixel. Furthermore, the ratio of the detection intensity of Ca to the detection intensity of Ni was calculated as the normalized intensity I of Ca. Ca The ratio of the detection intensity of Sr to the detection intensity of Ni is taken as the normalized intensity of Sr I Sr .

[0047] The range from the surface of the secondary particle to the inner side of 0.5 μm identified in the above image is regarded as the surface of the secondary particle, and the pixels contained in the surface of the secondary particle (hereinafter referred to as surface pixels) are determined. Ca The collection becomes I Ca_OUT , corresponding to the I of each surface pixel Sr The collection becomes I Sr_OUT In addition, the inner side of the secondary particle surface determined in the above is regarded as the inner side of the secondary particle, and the pixels contained in the inner side of the secondary particle (hereinafter referred to as inner pixels) are determined. The I corresponding to each inner pixel Ca The collection becomes I Ca_IN , the set of ISr corresponding to each surface pixel becomes I Sr_IN . The I obtained in this way Ca_OUT ,I Sr_OUT ,I Ca_IN and I Sr_IN , the Gini coefficient of Ca on the surface of the secondary particles, the Gini coefficient of Sr on the surface of the secondary particles, the Gini coefficient of Ca inside the secondary particles, and the Gini coefficient of Sr inside the secondary particles are calculated respectively. The sample for cross-sectional observation may be a sample in which a lithium transition metal composite oxide is embedded in a resin or the like, or may be a positive electrode mixture layer containing a lithium transition metal composite oxide.

[0048] The lithium transition metal composite oxide may have a layered structure. As the layered structure of the lithium transition metal composite oxide, for example, a layered structure belonging to the space group R-3m, a layered structure belonging to the space group C2 / m, etc. can be cited. From the viewpoint of high capacity and stability of the crystal structure, the lithium transition metal composite oxide preferably has a layered structure belonging to the space group R-3m. The layered structure of the lithium transition metal composite oxide may include a transition metal layer, a Li layer, and an oxygen layer.

[0049] In the layered structure of the lithium transition metal composite oxide, the ratio of the metal element other than Li present in the Li layer is 8 mol% or less relative to the total molar number of the metal elements other than Li in the lithium transition metal composite oxide. When the ratio of the metal element other than Li in the Li layer exceeds 8 mol%, the diffusivity of the Li ions in the Li layer decreases, and the battery capacity sometimes decreases. The metal element other than Li present in the Li layer is mainly Ni, but other metal elements may also be included. The ratio of the metal element other than Li in the Li layer is, for example, 0.1 mol% or more.

[0050] The ratio of metal elements other than Li in the layered Li layer is obtained from the Rietveld analysis results of the X-ray diffraction spectrum of the lithium transition metal composite oxide by X-ray diffraction measurement. For example, PDXL2 (Rigaku Corporation), which is a Rietveld analysis software, can be used for the Rietveld analysis of the X-ray diffraction spectrum.

[0051] The X-ray diffraction spectrum was obtained by powder X-ray diffraction under the following conditions using a powder X-ray diffractometer (manufactured by Rigaku Corporation, trade name "RINT-TTR", radiation source: Cu-Kα).

[0052] Measuring range: 15-120°

[0053] Scanning speed: 4° / min

[0054] Resolution range: 30-120°

[0055] Background: B-Splines

[0056] Curve function: segmented pseudo-Voigt function

[0057] Constraint: Li(3a)+Ni(3a)=1

[0058] Ni(3a)+Ni(3b)=α (α is the Ni content ratio of each)

[0059] ICSD No.:98-009-4814

[0060] The positive electrode mixture layer may contain other positive electrode active materials in addition to the positive electrode active material of the present embodiment. As other positive electrode active materials, for example, lithium transition metal composite oxides containing Ni, Ca and Sr, and having a Gini coefficient of more than 0.7 on the surface of secondary particles of Ca and Sr; and lithium transition metal composite oxides having a Gini coefficient of more than 0.6 inside the secondary particles of Ca and Sr.

[0061] Next, an example of a method for producing a positive electrode active material according to the present embodiment is described. The method for producing a positive electrode active material includes, for example, the following steps: a step of mixing a metal oxide containing at least Ni with a Li raw material, a Ca raw material, and a Sr raw material to obtain a mixture; and a step of calcining the mixture to obtain a positive electrode active material.

[0062] The metal oxide containing at least Ni can be prepared as follows: while stirring a solution containing a metal salt of Ni, Co, Al, Mn, etc., while dropping an alkaline solution such as sodium hydroxide, adjusting the pH to alkaline (e.g., 8.5 to 12.5), thereby precipitating a composite hydroxide (coprecipitation), and heat-treating the metal hydroxide, thereby preparing the metal oxide. The calcination temperature is not particularly limited, for example, in the range of 300° C. to 600° C.

[0063] Next, a metal oxide containing at least Ni is mixed with a Li raw material, a Ca raw material, and a Sr raw material to obtain a mixture. Examples of Li raw materials include Li2CO3, LiOH, Li2O2, Li2O, LiNO3, LiNO2, Li2SO4, LiOH·H2O, LiH, and LiF. Examples of Ca raw materials include Ca(OH)2, CaHPO4, Ca(H2PO4)2, Ca3(PO4)2, CaO, CaCO3, CaSO4, Ca(NO3)2, CaCl2, and CaAlO4. Examples of Sr raw materials include Sr(OH)2, SrHPO4, Sr(H2PO4)2, Sr3(PO4)2, SrO, SrCO3, SrSO4, Sr(NO3)2, SrCl2, and SrAlO4. In addition, during the mixing, a Me raw material may be mixed. As Me raw materials, Nb2O5, TiO2, ZrO2, WO3, SiO2 and the like can be cited.

[0064] By calcining the above mixture, a lithium transition metal composite oxide as a positive electrode active material is obtained. The mixture is calcined, for example, in an oxygen atmosphere. The calcination conditions are as follows: the first heating rate of 300°C or more and 680°C or less exceeds 1.0°C / minute and is in the range of 4.5°C / minute or less, and the maximum temperature reaches a range of 700°C or more and 850°C or less. The second heating rate from 680°C to the maximum temperature can be set to 0.1°C / minute to 3.5°C / minute, for example. In addition, the holding time to reach the maximum temperature can be more than 1 hour and less than 10 hours. In addition, the calcination process can be a multi-stage calcination, as long as the first heating rate and the second heating rate are within the above-defined range, and multiple can be set in each temperature zone. For example, by increasing the temperature at a lower rate, the dispersion of Ca and Sr is promoted, and the value of the Gini coefficient of Ca and Sr on the surface of the secondary particles and inside the secondary particles can be reduced.

[0065] The prepared lithium transition metal composite oxide can be washed with water and dried later. The washing with water and drying can be carried out under known methods and conditions. It should be noted that a Ca raw material, an Sr raw material or a Me raw material can be added to the filter cake-like composition after washing with water.

[0066] [Negative electrode]

[0067] The negative electrode 12 has, for example, a negative electrode current collector and a negative electrode mixture layer formed on the surface of the negative electrode current collector. The negative electrode mixture layer is preferably formed on both sides of the negative electrode current collector. As the negative electrode current collector, a foil of a metal such as copper or a copper alloy that is stable within the potential range of the negative electrode 12, a thin film having such a metal disposed on the surface layer, etc. can be used. The thickness of the negative electrode current collector is, for example, 5 μm to 30 μm. The negative electrode mixture layer contains, for example, a negative electrode active material and a binder. The thickness of the negative electrode mixture layer is, for example, 10 μm to 150 μm on one side of the negative electrode current collector. The negative electrode 12 can be produced, for example, as follows: A negative electrode mixture slurry containing a negative electrode active material, a binder, etc. is coated on the surface of the negative electrode current collector, and after the coating film is dried, rolling is carried out to form a negative electrode mixture layer on both sides of the negative electrode current collector, whereby it can be produced.

[0068] As the negative electrode active material contained in the negative electrode mixture layer, there is no particular limitation as long as it can reversibly store and release lithium ions, and carbon materials such as graphite are usually used. The graphite can be any of natural graphite such as flake graphite, massive graphite, earthy graphite, massive artificial graphite, graphitized mesophase carbon microbeads, etc. artificial graphite. In addition, as the negative electrode active material, metals alloyed with Li such as Si and Sn, metal compounds containing Si, Sn, etc., lithium titanium composite oxides, etc. can be used. In addition, those provided with a carbon coating film thereon can be used. For example, SiO x (0.5 ≤ x ≤ 1.6) shown Si-containing compound, or Li 2y SiO (2+y) A Si-containing compound in which fine particles of Si are dispersed in a lithium silicate phase shown by (0 < y < 2), etc. can be used in combination with graphite.

[0069] As the binder contained in the negative electrode mixture layer, for example, styrene-butadiene rubber (SBR), nitrile-butadiene rubber (NBR), carboxymethyl cellulose (CMC) or its salt, polyacrylic acid (PAA) or its salt (which can be PAA-Na, PAA-K, etc., and partially neutralized salts), polyvinyl alcohol (PVA), etc. can be cited. They can be used alone or in combination of two or more.

[0070] [Separator]

[0071] For example, a porous sheet having ion permeability and insulation is used in the separator 13. Specific examples of the porous sheet include microporous films, woven fabrics, nonwoven fabrics, etc. Suitable materials for the separator include polyolefins such as polyethylene and polypropylene, cellulose, etc. The separator 13 may have a single-layer structure or a laminated structure. In addition, a resin layer with high heat resistance such as an aromatic polyamide resin or a filler layer containing a filler of an inorganic compound may be provided on the surface of the separator 13.

[0072] [Non-aqueous electrolyte]

[0073] The non-aqueous electrolyte, for example, comprises a non-aqueous solvent and an electrolyte salt dissolved in the non-aqueous solvent. For example, esters, ethers, nitriles such as acetonitrile, amides such as dimethylformamide, and mixed solvents of two or more thereof can be used in the non-aqueous solvent. The non-aqueous solvent can contain a halogen substituted body formed by replacing at least a portion of the hydrogen atoms of these solvents with a halogen atom such as fluorine. As the halogen substituted body, fluorinated cyclic carbonates such as fluorinated ethylene carbonate (FEC), fluorinated chain carbonates, fluorinated chain carboxylates such as methyl fluoropropionate (FMP), etc. can be cited.

[0074] Examples of the above-mentioned esters include cyclic carbonates such as ethylene carbonate (EC), propylene carbonate (PC), and butylene carbonate, chain carbonates such as dimethyl carbonate (DMC), ethyl methyl carbonate (EMC), diethyl carbonate (DEC), methyl propyl carbonate, ethyl propyl carbonate, and methyl isopropyl carbonate, cyclic carboxylates such as γ-butyrolactone (GBL) and γ-valerolactone (GVL), and chain carboxylates such as methyl acetate, ethyl acetate, propyl acetate, methyl propionate (MP), and ethyl propionate.

[0075] Examples of the ethers include 1,3-dioxolane, 4-methyl-1,3-dioxolane, tetrahydrofuran, 2-methyltetrahydrofuran, propylene oxide, 1,2-butylene oxide, 1,3-dioxane, 1,4-dioxane, 1,3,5-trioxane, furan, 2-methylfuran, 1,8-cineole, cyclic ethers such as crown ethers, 1,2-dimethoxyethane, diethyl ether, dipropyl ether, diisopropyl ether, dibutyl ether. , dihexyl ether, ethyl vinyl ether, butyl vinyl ether, methyl phenyl ether, ethyl phenyl ether, butyl phenyl ether, pentyl phenyl ether, methoxytoluene, benzyl ethyl ether, diphenyl ether, dibenzyl ether, o-dimethoxybenzene, 1,2-diethoxyethane, 1,2-dibutoxyethane, diethylene glycol dimethyl ether, diethylene glycol diethyl ether, diethylene glycol dibutyl ether, 1,1-dimethoxymethane, 1,1-diethoxyethane, triethylene glycol dimethyl ether, tetraethylene glycol dimethyl ether and other chain ethers, etc.

[0076] The electrolyte salt is preferably a lithium salt. As examples of the lithium salt, LiBF4, LiClO4, LiPF6, LiAsF6, LiSbF6, LiAlCl4, LiSCN, LiCF3SO3, LiCF3CO2, Li(P(C2O4)F4), LiPF 6-x (C n F 2n+1 ) x (1 < x < 6, n is 1 or 2), LiB 10 Cl 10 、LiCl、LiBr、LiI、 lithium chloroborane, lithium lower aliphatic carboxylate, borate salts such as Li2B4O7, Li(B(C2O4)F2), imide salts such as LiN(SO2CF3)2, LiN(C1F 2l+1 SO2)(C m F 2m+1 SO2){l, m are integers of 0 or more}

[0077] and so on. The lithium salt can be used alone or in combination of multiple kinds. Among these, from the viewpoints of ionic conductivity, electrochemical stability, etc., LiPF6 is preferably used. The concentration of the lithium salt is, for example, 0.5 mol to 2 mol per 1 L of the non-aqueous solvent. In addition, vinylene carbonate, propanesultone-based additives can be further added.

[0078] Examples

[0079] Hereinafter, the present disclosure will be further described based on examples and comparative examples, but the present disclosure is not limited to the following examples.

[0080] <Example 1-1>

[0081] [Production of positive electrode active material]

[0082] The composite hydroxide represented by [Ni 0.90 Co 0.05 Al 0.05 (OH)2 obtained by the coprecipitation method was calcined at 500 °C for 8 hours to obtain a metal oxide (Ni 0.90 Co 0.05 Al 0.05O2). Next, Ca(OH)2 and Sr(OH)2 are added to the above metal oxides in such a manner that the molar ratio of Ca is 0.25 mol% and the molar ratio of Sr is 0.05 mol% relative to the total amount of Ni, Co and Al, and lithium hydroxide monohydrate (LiOH·H2O) is mixed in such a manner that the molar ratio of Li relative to the total amount of Ni, Co, Al, Ca and Sr is 103 mol% to obtain a mixture. The mixture is calcined from room temperature to 650°C at a first heating rate of 2°C / min under an oxygen gas flow with an oxygen concentration of 95% (a flow rate of 5 L / min per 1 kg of the mixture), and then calcined from 650°C to 720°C at a second heating rate of 1°C / min to obtain a lithium transition metal composite oxide. The lithium transition metal composite oxide is washed with water and dried to obtain the positive electrode active material of Example 1-1.

[0083] The positive electrode active material was measured using an ICP emission spectrophotometer (ICP-AES), and the elements shown in Table 1 described below were confirmed as elements other than Li and O. The element concentration distribution of the cross section of the positive electrode active material was measured according to time-of-flight secondary ion mass spectrometry (TOF-SIMS), and the Gini coefficients of the secondary particle surfaces of Ca and Sr were 0.60 and 0.58, respectively, and the Gini coefficients of the secondary particles of Ca and Sr were 0.33 and 0.56, respectively. The ratio of the metal elements other than Li present in the Li layer is 2.0 mol% relative to the total molar number of the metal elements other than Li in the aforementioned lithium transition metal composite oxide.

[0084] [Production of positive electrode]

[0085] 95 parts by mass of the above-mentioned positive electrode active material are mixed with 3 parts by mass of acetylene black (AB) and 2 parts by mass of polyvinylidene fluoride (PVDF), and an appropriate amount of N-methyl-2-pyrrolidone (NMP) is further added to prepare a positive electrode mixture slurry. Next, the positive electrode mixture slurry is applied to both sides of a positive electrode collector formed of aluminum foil with a thickness of 15 μm, and after the coating is dried, the coating is rolled using a calendering roller, cut into a specified electrode size, and a positive electrode is prepared. It should be noted that a portion of the positive electrode is provided with an exposed portion exposed on the surface of the positive electrode collector.

[0086] [Production of negative electrode]

[0087] Natural graphite is used as the negative electrode active material. The negative electrode active material is mixed with sodium carboxymethyl cellulose (CMC-Na) and styrene-butadiene rubber (SBR) in an aqueous solution at a solid content mass ratio of 100:1:1 to prepare a negative electrode mixture slurry. Next, the negative electrode mixture slurry is applied to both sides of a negative electrode collector formed of copper foil, and after the coating film is dried, the coating film is rolled using a calendering roller and cut into a specified electrode size to produce a negative electrode. It should be noted that a portion of the negative electrode is provided with an exposed portion where the surface of the negative electrode collector is exposed.

[0088] [Preparation of non-aqueous electrolyte]

[0089] Ethylene carbonate (EC), ethyl methyl carbonate (EMC), and dimethyl carbonate (DMC) were mixed at a volume ratio of 3:3:4. Lithium hexafluorophosphate (LiPF6) was dissolved in the mixed solvent to a concentration of 1.2 mol / L to prepare a non-aqueous electrolyte.

[0090] [Production of test battery cells]

[0091] The positive electrode lead is installed on the exposed part of the positive electrode, and the negative electrode lead is installed on the exposed part of the negative electrode. The positive electrode and the negative electrode are wound into a spiral shape with a polyolefin separator interposed therebetween, and then pressurized and formed in the radial direction to produce a flat wound electrode body. The electrode body is housed in an outer shell composed of an aluminum laminate sheet, and after the above-mentioned non-aqueous electrolyte is injected, the opening of the outer shell is sealed to obtain a test battery cell.

[0092] [Evaluation of capacity maintenance rate]

[0093] At an ambient temperature of 25°C, the test battery cell was charged at a constant current of 0.3C to 4.2V, then charged at a constant voltage of 4.2V to 0.02C, and then discharged at a constant current of 0.5C to 2.5V. This charge and discharge was regarded as one cycle, and 300 cycles were performed. The capacity retention rate of the test battery cell in the charge and discharge cycle was calculated according to the following formula.

[0094] Capacity retention rate = (discharge capacity at the 300th cycle / discharge capacity at the 1st cycle) × 100

[0095] [Evaluation of DCIR increase rate]

[0096] At an ambient temperature of 25°C, the test battery cell was charged at a constant current of 0.3C until it reached 4.2V, and then charged at a constant voltage of 4.2V until it reached 0.02C. After that, the test battery cell was left to stand for 2 hours, and then discharged at a constant current of 0.5C for 10 seconds. The open circuit voltage (OCV), the closed circuit voltage (CCV) 10 seconds after the discharge, and the current value (I10s ), calculate the DC resistance (DCIR) according to the following formula and use this value as the initial DCIR.

[0097] DCIR=(OCV-CCV) / I 10s

[0098] Next, at an ambient temperature of 25°C, the test cell was charged at a constant current of 0.3C to 4.2V, then charged at a constant voltage of 4.2V to 0.02C, and then discharged at a constant current of 0.5C to 2.5V. This charge and discharge was regarded as one cycle, and 300 cycles were performed.

[0099] For the secondary battery after 300 cycles, the DCIR was calculated in the same manner as the initial DCIR, and the value was defined as the post-cycle DCIR. The DCIR increase rate was determined from the initial DCIR and the post-cycle DCIR using the following formula.

[0100] DCIR increase rate (%) = (DCIR after cycle - initial DCIR) / initial DCIR × 100

[0101] <Examples 1-2 to 1-5>

[0102] In the preparation of the positive electrode active material, the amount of Ca(OH)2 and Sr(OH)2 added was changed in such a manner that the molar ratio of Ca and Sr relative to the total amount of Ni, Co and Al became the value shown in Table 1. For Examples 1-3 to 1-5, ZrO2, TiO2 or Nb2O5 was added in such a manner that the molar ratio of Zr, Ti or Nb relative to the total amount of Ni, Co and Al became the value shown in Table 1 to prepare a mixture. Except for this, a test battery cell was prepared and evaluated in the same manner as in Example 1-1.

[0103] <Example 1-6>

[0104] In the preparation of the positive electrode active material, the amounts of Ca(OH)2 and Sr(OH)2 added were changed so that the molar ratio of Ca became 0.20 mol% and the molar ratio of Sr became 0.10 mol% relative to the total amount of Ni, Co and Al, and CaCl2 was added to the cake-like composition after washing with water so that 0.05 mol% of Ca was added relative to the total amount of Ni, Co and Al. Apart from this, a test battery cell was prepared and evaluated in the same manner as in Example 1-1.

[0105] <Example 1-7>

[0106] In the preparation of the positive electrode active material, the amounts of Ca(OH)2 and Sr(OH)2 added were changed in such a way that the molar ratio of Ca became 0.25 mol% and the molar ratio of Sr became 0.05 mol% relative to the total amount of Ni, Co and Al, and SrCl2 was added to the cake-like composition after water washing in such a way that 0.05 mol% Sr was added relative to the total amount of Ni, Co and Al, and the second heating rate was changed to 0.5°C / min. Apart from this, a test battery cell was prepared and evaluated in the same manner as Example 1-1.

[0107] <Comparative Examples 1-1 to 1-4>

[0108] In the preparation of the positive electrode active material, the amount of added Ca(OH)2 and Sr(OH)2 was changed in such a way that the molar ratio of Ca and Sr relative to the total amount of Ni, Co and Al became the value shown in Table 1, the first heating rate was changed to 5°C / min, and the second heating rate was changed to 3°C / min. Apart from this, a test battery cell was prepared and evaluated in the same manner as Example 1-1.

[0109] <Comparative Example 1-5>

[0110] Ca(OH)2 was added to the metal oxide, and Sr(OH)2 was not added. Sr(OH)2 was added to the cake-like composition after water washing in such a way that the molar ratio of Sr relative to the total amount of Ni, Co and Al became the value shown in Table 1. The first heating rate was changed to 5°C / min, and the second heating rate was changed to 3°C / min. Except for this, a test battery cell was prepared and evaluated in the same manner as Example 1-1.

[0111] <Comparative Example 1-6>

[0112] In the preparation of the positive electrode active material, the amount of added Sr(OH)2 was changed in such a manner that the molar ratio of Sr relative to the total amount of Ni, Co and Al became the value shown in Table 1, and Ca(OH)2 was not added. Ca(OH)2 was added to the cake-like composition after washing in such a manner that the molar ratio of Ca relative to the total amount of Ni, Co and Al became the value shown in Table 1. The first heating rate was changed to 5°C / min, and the second heating rate was changed to 3°C / min. Except for this, a test battery cell was prepared and evaluated in the same manner as Example 1-1.

[0113] <Example 2-1>

[0114] In the preparation of the positive electrode active material, the composition of the metal oxide is changed to Ni 0.93 Al 0.04 Mn 0.03Ca(OH)2 and Sr(OH)2 were added in such a manner that the molar ratio of Ca became 0.30 mol% and the molar ratio of Sr became 0.09 mol% relative to the total amount of Ni, Al and Mn. Otherwise, a test battery cell was prepared and evaluated in the same manner as in Example 1-1.

[0115] <Examples 2-2 to 2-4>

[0116] In the preparation of the positive electrode active material, ZrO2, TiO2 or Nb2O5 is further added in such a manner that the molar ratio of Zr, Ti or Nb relative to the total amount of Ni, Al and Mn becomes the value shown in Table 2 to prepare a mixture. Otherwise, a test battery cell is prepared and evaluated in the same manner as in Example 2-1.

[0117] <Comparative Examples 2-1 to 2-2>

[0118] In the preparation of the positive electrode active material, the amount of added Ca(OH)2 and Sr(OH)2 was changed in such a way that the molar ratio of Ca and Sr relative to the total amount of Ni, Al and Mn became the value shown in Table 2, the first heating rate was changed to 5°C / min, and the second heating rate was changed to 3°C / min. Apart from this, a test battery cell was prepared and evaluated in the same manner as Example 2-1.

[0119] <Example 3-1>

[0120] In the preparation of the positive electrode active material, the composition of the metal oxide is changed to Ni 0.90 Co 0.04 Mn 0.06 Ca(OH)2 and Sr(OH)2 were added in such a manner that the molar ratio of Ca became 0.27 mol% and the molar ratio of Sr became 0.09 mol% relative to the total amount of Ni, Co and Mn. Otherwise, a test battery cell was prepared and evaluated in the same manner as in Example 1-1.

[0121] <Examples 3-2 to 3-8>

[0122] In the preparation of the positive electrode active material, Nb2O5, ZrO2, WO3, TiO2 or SiO2 is added in such a manner that the molar ratio of Nb, Zr, W, Ti or Si relative to the total amount of Ni, Co and Mn becomes the value shown in Table 3 to prepare a mixture. Except for this, a test battery cell is prepared and evaluated in the same manner as Example 3-1.

[0123] <Comparative Examples 3-1 to 3-2>

[0124] In the preparation of the positive electrode active material, the amount of added Ca(OH)2 and Sr(OH)2 was changed in such a way that the molar ratio of Ca and Sr relative to the total amount of Ni, Co and Mn became the value shown in Table 3, the first heating rate was changed to 5°C / min, and the second heating rate was changed to 3°C / min. Apart from this, a test battery cell was prepared and evaluated in the same manner as Example 3-1.

[0125] <Example 4-1>

[0126] In the preparation of the positive electrode active material, the composition of the metal oxide is changed to Ni 0.90 Mn 0.10 Ca(OH)2 and Sr(OH)2 were added in such a manner that the molar ratio of Ca became 0.28 mol% and the molar ratio of Sr became 0.10 mol% relative to the total amount of Ni and Mn. Otherwise, a test battery cell was prepared and evaluated in the same manner as in Example 1-1.

[0127] <Examples 4-2 to 4-6>

[0128] In the preparation of the positive electrode active material, Nb2O5, ZrO2, WO3, TiO2 or SiO2 is added in such a manner that the molar ratio of Nb, Zr, W, Ti or Si relative to the total amount of Ni and Mn becomes the value shown in Table 4 to prepare a mixture. Except for this, a test battery cell is prepared and evaluated in the same manner as Example 4-1.

[0129] <Comparative Examples 4-1 to 4-2>

[0130] In the preparation of the positive electrode active material, the amount of added Ca(OH)2 and Sr(OH)2 was changed in such a way that the molar ratio of Ca and Sr relative to the total amount of Ni and Mn became the value shown in Table 4, the first heating rate was changed to 5°C / min, and the second heating rate was changed to 3°C / min. Apart from this, a test battery cell was prepared and evaluated in the same manner as Example 4-1.

[0131] The evaluation results of the test battery cells of the embodiments and comparative examples are shown in Tables 1 to 4. In addition, Tables 1 to 4 each show the composition of the metal oxide used when making the positive electrode active material, the ratio of the additives, the Gini coefficient, and the ratio of the metal elements other than Li in the Li layer. In Table 1, the capacity retention rate and DCIR increase rate of the test battery cells other than Comparative Example 1-1 are expressed relative to the capacity retention rate and DCIR increase rate of the test battery cells of Comparative Example 1-1 as 100. In Table 2, the capacity retention rate and DCIR increase rate of the test battery cells other than Comparative Example 2-1 are expressed relative to the capacity retention rate and DCIR increase rate of the test battery cells of Comparative Example 2-1 as 100. In Table 3, the capacity retention rate and DCIR increase rate of the test battery cells other than Comparative Example 3-1 are expressed relative to the capacity retention rate and DCIR increase rate of the test battery cells of Comparative Example 3-1 as 100. In Table 4, the capacity maintenance rate and DCIR increase rate of the test battery cells other than Comparative Example 4-1 are expressed relatively, with the capacity maintenance rate and DCIR increase rate of the test battery cell of Comparative Example 4-1 being 100, respectively.

[0132] [Table 1]

[0133]

[0134] [Table 2]

[0135]

[0136] [Table 3]

[0137]

[0138] [Table 4]

[0139]

[0140] In Tables 1 to 4, the test battery cells of the embodiments have a higher capacity retention rate and a lower DCIR increase rate than the test battery cells of the comparative examples. It can be seen that by including a lithium transition metal composite oxide having a Gini coefficient of 0.7 or less on the surface of the secondary particles of Ca and Sr and a Gini coefficient of 0.6 or less inside the secondary particles of Ca and Sr in the positive electrode active material, the charge and discharge cycle characteristics are improved and the increase in resistance is suppressed.

[0141] The present disclosure will be further described based on the following embodiments.

[0142] Composition 1:

[0143] A positive electrode active material for a non-aqueous electrolyte secondary battery, comprising a lithium transition metal composite oxide,

[0144] The lithium transition metal composite oxide contains Ni, Ca and Sr and includes secondary particles formed by aggregation of primary particles.

[0145] In the element concentration distribution of the cross section of the lithium transition metal composite oxide using time-of-flight secondary ion mass spectrometry,

[0146] The Gini coefficients of the surfaces of the secondary particles of Ca and Sr are 0.7 or less, and the Gini coefficients of the interiors of the secondary particles of Ca and Sr are 0.6 or less.

[0147] Composition 2:

[0148] The positive electrode active material for a non-aqueous electrolyte secondary battery according to configuration 1, wherein the content of Ni in the lithium transition metal composite oxide is 80 mol % or more relative to the total number of moles of metal elements other than Li in the lithium transition metal composite oxide.

[0149] Composition 3:

[0150] The positive electrode active material for a non-aqueous electrolyte secondary battery according to configuration 1 or 2, wherein

[0151] The lithium transition metal composite oxide has a layered structure.

[0152] The ratio of the metal element other than Li present in the Li layer of the layered structure is 8 mol% or less relative to the total number of moles of the metal element other than Li in the lithium transition metal composite oxide.

[0153] Composition 4:

[0154] The positive electrode active material for a non-aqueous electrolyte secondary battery according to any one of Configurations 1 to 3, wherein the lithium-transition metal composite oxide further contains one or more elements selected from the group consisting of Co, Al, and Mn.

[0155] Composition 5:

[0156] The positive electrode active material for a non-aqueous electrolyte secondary battery according to any one of Configurations 1 to 4, wherein the lithium-transition metal composite oxide further contains one or more elements selected from the group consisting of Nb, Ti, Zr, W, and Si.

[0157] Composition 6:

[0158] A nonaqueous electrolyte secondary battery comprises: a positive electrode containing the positive electrode active material for a nonaqueous electrolyte secondary battery according to any one of configurations 1 to 5, a negative electrode, and a nonaqueous electrolyte.

[0159] Description of Reference Numerals

[0160] 10 secondary battery, 11 positive electrode, 12 negative electrode, 13 separator, 14 electrode body, 16 outer shell, 17 sealing body, 18, 19 insulating plate, 20 positive electrode lead, 21 negative electrode lead, 22 groove portion, 23 internal terminal plate, 24 lower valve body, 25 insulating member, 26 upper valve body, 27 cover, 28 gasket.

Claims

1. A positive electrode active material for a non-aqueous electrolyte secondary battery, comprising a lithium transition metal composite oxide, The lithium transition metal composite oxide contains Ni, Ca and Sr and includes secondary particles formed by aggregation of primary particles. In the element concentration distribution of the cross section of the lithium transition metal composite oxide using time-of-flight secondary ion mass spectrometry, The Gini coefficients of the surfaces of the secondary particles of Ca and Sr are 0.7 or less, and the Gini coefficients of the interiors of the secondary particles of Ca and Sr are 0.6 or less.

2. The positive electrode active material for a non-aqueous electrolyte secondary battery according to claim 1, wherein The content of Ni in the lithium transition metal composite oxide is 80 mol % or more relative to the total number of moles of metal elements other than Li in the lithium transition metal composite oxide.

3. The positive electrode active material for a non-aqueous electrolyte secondary battery according to claim 1, wherein The lithium transition metal composite oxide has a layered structure. The ratio of the metal element other than Li present in the Li layer of the layered structure is 8 mol % or less relative to the total number of moles of the metal element other than Li in the lithium transition metal composite oxide.

4. The positive electrode active material for a non-aqueous electrolyte secondary battery according to claim 1, wherein The lithium transition metal composite oxide further contains one or more elements selected from the group consisting of Co, Al, and Mn.

5. The positive electrode active material for a non-aqueous electrolyte secondary battery according to claim 1, wherein The lithium transition metal composite oxide further includes one or more elements selected from the group consisting of Nb, Ti, Zr, W, and Si. 6 . A non-aqueous electrolyte secondary battery comprising: a positive electrode comprising the positive electrode active material for a non-aqueous electrolyte secondary battery according to claim 1 , a negative electrode, and a non-aqueous electrolyte.

Citation Information

Patent Citations

  • All season type cooling, dehumidifying and heating device for use in painting

    JP1987026430A